Toxicity of Barringtonia racemosa (L.) Kernel Extract on Pomacea canaliculata (Ampullariidae) - Musri Musman (Tropical Life Sciences Research, 2010)
A number of tropical plant species have been recognised as molluscicidal plants, and Barringtonia racemosa (L.) is one of these. The toxicity effects of B. racemosa seed kernel extracts on Pomacea canaliculata were evaluated. The lethal concentration at 50% [LC50 (lower-upper limits)] values, in ppm/48 hours, were 70.71 (41.33–120.97), 94.39 (62.48–142.59), 186.84 (129.21–270.17), and 672.72 (366.57–1234.53) for the extracts withdrawn using dichloromethane (DCM), methanol (MeOH), ethyl acetate (EtOAc), heptane (hp) solvents, respectively at 95% confidence interval (C. I.). All analyses were conducted using Trimmed Spearman-Karber (TSK) program version 1.5. It is assumed that the observed biological effects of the extracts may be due to the saponins and flavonoids present in the seed. The dichloromethanic and methanolic extracts contain saponin and flavonoid substances. Therefore these extracts have shown more potent molluscicidal activity towards the tested organism compared to the remaining extracts. This observed biological activity suggests a promising role for B. racemosa in the control of P. canaliculata. Beberapa spesies tumbuhan tropika telah dikenalpasti sebagai anti moluska dan Barringtonia racemosa (L.) ialah salah satu daripadanya. Kesan racun ekstrak biji benih B. racemosa terhadap Pomacea canaliculata telah dikaji. Lethal concentration pada 50% [LC50 (lower-upper limits)] dalam ppm/48 jam ialah 70.71 (41.33–120.97), 94.39 (62.48– 142.59), 186.84 (129.21–270.17), dan 672.72 (366.57–1234.53) bagi ekstrak diklorometan (DCM), methanol (MeOH), etil asetat (EtOAc), dan heptan (hp) pada 95% confidence interval (C. I.) masing-masing. Semua analisis dijalankan menggunakan program Trimmed Spearman-Karber (TSK) versi 1.5. Diandaikan bahawa kesan biologi adalah disebabkan oleh saponin dan flavonoid yang terkandung dalam biji benih B. racemosa. Ekstrak DCM dan MeOH yang mengandungi saponin dan flavonoid memberikan kesan molusisida yang lebih baik berbanding dengan ekstrak pelarut yang lain. Aktiviti biologi yang diperhatikan mencadangkan bahawa B. racemosa berpotensi dalam pengawalan P. canaliculata.